Strain analysis in the drilling of human and bovine bone - Fernandes, M.G.A. (2018)
The growing importance of boné surgical drilling procedures hás moíivated the development ofassessment methods aimed to preveni boné injiiry. Different studies on the parameters influencing boné drilling have been published. However, most of the results are based only in the analysis of temperatures. There is a lack of information on the mechanical damage on boné, especially about boné tissue swface integrity and the strain distribution during drilling. The challenge diiring drilling should not be Umited to avoid thermal damage but also to predict the strains qffècting the boné, since the cutting force and lhe accuracy of the osíeotomy depends upon the sin-geon 's manual skills.